Design and implementation of a blind stick integrated with sensors and audio assistance for visually impaired people - Amin, Md. Al; Paul, Amlan; Hasan, Md. Abid; Imtiaz, Kazi Saklain (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.